Freedom of contract: an overview / Abd. Hamid Abdul Karim - Abdul Karim, Abd. Hamid (Faculty of Law, 1987)
The paper deals with the discussion on the perspective of Freedom of Contract. In the introduction the writer has discussed the purpose, scope and limitation of study. Due to limited time and space the writer has limited the study on the out line of the Freedom of Contract and its restrictions. The writer has also laid down the rationale behind the restrictioos on the Freedom of Contract. Most of the materials in the writing of this paper were collected through research and references made from various textbooks, journals and articles which provided invaluable primary sources. Limited time and finance for the project paper presents a setback. Therefore the scope and details of the study are presented selectively in order to maintain a reasonable length.